Established Beta Amyloid Pathology Is Unaffected by TREM2 Elevation in Reactive Microglia in an Alzheimer’s Disease Mouse Model - Qiuju Yuan; Xiaodong Liu; Yi Zhang; Yan-Fang Xian; Juntao Zou; Xie Zhang; Pengyun Huang; You-Qiang Song; Zhi-Xiu Lin (Molecules, 2021)
Several genetic studies have identified a rare variant of triggering receptor expressed on myeloid cells 2 (TREM2) as a risk factor for Alzheimer’s disease (AD). However, findings on the effects of TREM2 on Aβ deposition are quite inconsistent in animal studies, requiring further investigation. In this study, we investigated whether elevation of TREM2 mitigates Aβ pathology in TgCRND8 mice. We found that peripheral nerve injury resulted in a robust elevation of TREM2 exclusively in reactive microglia in the ipsilateral spinal cord of aged TgCRND8 mice at the age of 20 months. TREM2 expression appeared on day 1 post-injury and the upregulation was maintained for at least 28 days. Compared to the contralateral side, neither amyloid beta plaque load nor soluble Aβ40 and Aβ42 levels were attenuated upon TREM2 induction. We further showed direct evidence that TREM2 elevation in reactive microglia did not affect amyloid-β pathology in plaque-bearing TgCRND8 mice by applying anti-TREM2 neutralizing antibody to selectively block TREM2. Our results question the ability of TREM2 to ameliorate established Aβ pathology, discouraging future development of disease-modifying pharmacological treatments targeting TREM2 in the late stage of AD.